Tracked Changes. Covered conductors for overhead lines and the related accessories for rated voltages above 1 kV a.c. and not exceeding 36 kV a.c. Accessories for covered conductors. Tests and acceptance criteria Part 2, (16th January 2023) - British Standards Institution,
No abstract available